2022
DOI: 10.1109/access.2022.3185788
|View full text |Cite
|
Sign up to set email alerts
|

DC Integration of Residential Photovoltaic Systems: A Survey

Abstract: PV systems are penetrating the energy generation market rapidly. PV system output strongly depends on environmental conditions. As a result, the utilization of power electronic converters is mandatory. On the other hand, most modern loads, from small to big ones, are based on dc, similar to the renewable sources generating dc. Hence, wide adoption of residential dc microgrids (RDCμGs) based on PV energy would be a trend soon, following modern developments in energy-efficient buildings. This paper targets power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…Use Eqs. ( 9) & (10) Set the THD & qZSI Power losses final optimal state is x opt 42: end procedure MMPC is based on expanding the number of the checked switching states from 9 states in [33] to 15 states in the proposed scheme, accordingly, the number of For-Loops which is used to select the optimal operating switching state should be increased resulting in increasing the computation time. However, in this study, the computational burden has been reduced by utilizing calculation loop optimization by reducing the number of switching states in the loop and calculation loop unrolling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use Eqs. ( 9) & (10) Set the THD & qZSI Power losses final optimal state is x opt 42: end procedure MMPC is based on expanding the number of the checked switching states from 9 states in [33] to 15 states in the proposed scheme, accordingly, the number of For-Loops which is used to select the optimal operating switching state should be increased resulting in increasing the computation time. However, in this study, the computational burden has been reduced by utilizing calculation loop optimization by reducing the number of switching states in the loop and calculation loop unrolling.…”
Section: Resultsmentioning
confidence: 99%
“…But this also increases the cost and complexity of the control circuit and components. To overcome these problems, some researchers suggested using single-stage converters without transformers, based on new topologies called multi-level inverters [6], [7], [8], [9], [10]. These inverters use many power devices connected by passive and active switches, which require complex control circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Residential PV systems suffering from partial shading of PV modules need interface converters capable of global maximum power point tracking [97]. This feature requires those converters to ensure a wide input voltage range that could be achieved at a low cost using TMC [83].…”
Section: Promising Applicationsmentioning
confidence: 99%
“…However, later research showed they are equivalent to a full power boost converter in terms of stress of the main components and thus can not be considered true PPCs [34]. Hence, dc-dc topology used in a PPC must have some kind of galvanic isolation, either by a transformer or using a flying energy storage component (capacitor or inductor) [33], [35], [36].…”
Section: A Requirement Of Isolationmentioning
confidence: 99%